To analyse the correlation between UAER and eGFR and the risk factors for reducing eGFR in patients with type 2 diabetes - Haihui Li; Lanwen Han; Xia Gao (BMC Endocrine Disorders)
Abstract Objective To analyse the correlation between urinary albumin excretion rate (UAER) and estimated glomerular filtration rate (eGFR) and the risk factors for reducing eGFR in patients with type 2 diabetes mellitus (T2DM). Methods A total of 431 T2DM patients admitted between January 2019 and March 2020 were selected and divided into two groups according to eGFR level. Comparing the differences between baseline data and clinical indicators, multivariate logistic regression was used to analyse the risk factors of eGFR reduction and to analyse the association between UAER and eGFR. Results In total, 167 patients were included in the study group and 264 patients were included in the conventional group. The study group participants were older, had longer diabetes duration, and had higher fatty liver, peripheral vascular disease (PVD), hypertension prevalence, and mean body mass index (P < 0.05). The levels of various indicators were lower than those of the conventional group (P < 0. 05). Additionally, PVD, nocturnal systolic blood pressure, fatty liver, and beta-2-microglobulin (β 2-MG) were independent risk factors for eGFR decline, with high density lipoprotein (HDL) and fasting C-peptide (CP) as protective factors. There was no obvious correlation between UAER and eGFR. Conclusion Peripheral vascular disease, systolic blood pressure, fatty liver, and beta-2-microglobulin are risk factors for decreased eGFR levels in patients with T2DM, which should be applied for control DKD. HDL and fasting CP have important effects on maintaining eGFR, and blood pressure and fasting CP can be used as new targets for subsequent diabetic kidney disease treatment.